2013
DOI: 10.1111/j.1464-5491.2012.03771.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating problems in adolescents with Type 1 diabetes: a systematic review with meta‐analysis

Abstract: Eating problems are common among this age group. Future work in populations with Type 1 diabetes should develop sensitive measures of eating problems and interventions, and establish predictors of eating problems. Screening in clinics is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
272
3
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(321 citation statements)
references
References 38 publications
(87 reference statements)
14
272
3
20
Order By: Relevance
“…In studies from Jones et al (2) and Grylli et al (20), 10% and 11.5% of the investigated patients with T1DM had ED based on DSM-IV criteria. Recently, ED prevalence among adolescents with T1DM was estimated to 7.0% (35). In a metaanalysis of T1DM females, prevalence of AN was not significantly higher compared with nondiabetic control subjects; however, BN was reported significantly more often (5).…”
Section: Discussionmentioning
confidence: 99%
“…In studies from Jones et al (2) and Grylli et al (20), 10% and 11.5% of the investigated patients with T1DM had ED based on DSM-IV criteria. Recently, ED prevalence among adolescents with T1DM was estimated to 7.0% (35). In a metaanalysis of T1DM females, prevalence of AN was not significantly higher compared with nondiabetic control subjects; however, BN was reported significantly more often (5).…”
Section: Discussionmentioning
confidence: 99%
“…340 Disturbed eating behaviors, coupled with unhealthy weight control behaviors, have been associated with adverse glucose control. 338,341 Up to 50.4% of male and female adolescents with T1DM reported using weight control behaviors. 338 Insulin omission and insulin underdosing are the most serious weight control behaviors reported.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The interpretation of the reported prevalence of DEB and diabetes is difficult because there are no standardised diabetes-specific measures; however, it has been suggested that between 11.5% and 27.5% of adolescents with type 1 diabetes meet the diagnostic criteria for an ED, most commonly bulimia nervosa or binge eating disorder. 1,3 Up to 30% mismanage insulin to avoid weight gain or lose weight. 4 The most common risk factors for the development of an ED in the general population include young female, a history of dietary restraint and dieting, weight gain, low self-esteem, and family dysfunction.…”
Section: Eating Disorders and Diabetesmentioning
confidence: 99%
“…Almost 50 years later it is now well established that when compared with their non-diabetic peers, individuals with type 1 diabetes are at increased risk of developing disordered eating behaviours (DEBs) and EDs which are associated with poor glycaemic control. 1 Poor glycaemic control and its potentially life threatening impact on health, make it essential that diabetes health care teams are aware of the potential for disordered eating in conjunction with a preoccupation with weight and negative body image so that it can be recognised and treated early.…”
mentioning
confidence: 99%